A stranger in mayfair eaudiobook - Finch, Charles (Charles Lenox Mystery, 2011)
Returning from a continental honeymoon with his new wife, Lady Jane, Lenox is asked by a colleague in Parliament to consult in the murder of a footman, bludgeoned to death with a brick. His investigation uncovers some unsettling facts about the family he served and a strange, second identity that the footman himself cultivated. Going into the boxing clubs and public houses, the Mayfair mansions and servants' quarters of Victorian London, Lenox gradually realizes that an old friend may be implicated in the footman's death. Soon a suspect is arrested, but Lenox has his doubts. Desperately trying to balance the opening of Parliament and what he feels sure is a dark secret surrounding the murder, he soon discovers that the killer is someone seemingly beyond suspicion, and may be prepared to spill blood again—even a detective's.